IRRITANTCY POTENTIAL AND SUB ACUTE DERMAL TOXICITY STUDY OF PISTACIA LENTISCUS FATTY OIL AS A TOPICAL TRADITIONAL REMEDY. - DJERROU, Zouhir; Djaalab, Hadria; Riachi, Foulla; Serakta, Mennouba; Chettoum, Aziez; Maameri, zineb; Boutobza, Badaoui; Hamdi Pacha, Youcef (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The current study was undertaken to assess safety of Pistacia lentiscus fruits fatty oil(PLFO) as a topical traditional remedy. A primary skin and eye irritation tests were conducted withNew Zealand white rabbits to determine the potential for PLFO to produce irritation from a singleapplication. In addition, a sub acute dermal toxicity study was performed on 18 NZW rabbits toevaluate possible adverse effect following application of PLFO for 28 days.Based on the results of the current study, PLFO is classified as slightly irritating to the skinand the eye of rabbits (Primary Irritation Index (P.I.I.) = 1.037; ocular irritation index (O.I.I.) = 5.33at 1 h). In the sub acute toxicity test, PLFO produced neither mortality nor significant differences inthe body and organ weights between control group and treated rabbits. However, a reversibleirritant contact dermatitis was observed in the treated areas since the end of the second week ofapplication until the end of experiment. This local phenomenon was accompanied by a significantskin thickening (P≤0.01) since the 12th day (ANOVA, F = 11, 07143, P = 0, 00765) which isconfirmed with an inflammatory granuloma in histological study. Hematological analysis andblood chemistry values of the 2 groups showed no significant differences in any of the parametersexamined. In summary, PLFO is minimally irritating to the eye and skin after a single exposure, butit may cause irritant contact dermatitis and a reversible thichening of skin after prolonged use.Key words: Pistacia lentiscus, fatty oil, skin, eye, dermatitis, irritation, toxicity.